Study on the Coal-Water Fuel Pipeline Transportation Taking Into Account the Granulometric Composition Parameters - Chernetskaya-Beletskaya, N; Rogovyi, A; Shvornikova, A; Baranov, I; Miroshnikova, M; Bragin, N (International Journal of Engineering and Technology, 2018)
The highly loaded coal-water fuel pipe flow was verified. The move of the coal-water fuel with the 60% of coal loading practically has not been studied, especially for the coal originated from Ukraine. Through experimental research it was discovered that the water-coal fuel of such concentrations has a Bingham rheological characteristic. The verification was carried out by comparing the results of numerical calculations and experimental research. As a result of the numerical calculations of the flow, near the axis of the tube, a zone of approximately the same velocity is obtained, which qualitatively coincides with the results of experimental studies and with the results of the analytical description of the Bingham flow. As a result of the calculation the pressure drop value was defined, costs and velocity distribution over the cross section of the pipeline in the straight line and in curve. The velocity distribution profiles of the water-coal fuel flow are built. To compare the results of the calculation and to validate the rheological model choice velocity calculations were performed using the proposed model of Bingham and Newtonian fluids at the same effective viscosity values.
Keywords: Transportation; Coal-water fuel; Granulometric composition; Modeling; Rheological characteristics.